Personnel Management of The Indonesian National Army Air Force (TNI-AU) In Preparing To Implement Network Centric Warfare - Sudarya, Agus (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study attempts to describe the management of Indonesian Air Force (TNI-AU) personnel in preparing for the implementation of Network Centric Warfare (NCW). Globally, the military’s Information and Communication Technology (ICT) is growing. The war in this digital era makes every country need to prepare itself for the attacks of the digital world. In Indonesia itself, the Indonesian National Army (TNI) has included NCW as one of its programs to deal with possible disturbances in state security stability through the digital world. In addition, NCW is needed by the TNI as a form of a centralized and fast command communication strategy. This study uses a case study strategy involving five informants and written data to complete the integrity of the data. In personnel training management, the TNI-AU has prepared integrated infrastructure development, modeling and simulation, cyber defense management, and personnel management to be specially prepared to occupy crucial positions in the implementation of NCW. This personnel training concentrates on strengthening protection from foreign attacks in the digital world and the technology of unmanned warfare vehicles.